African-centered pedagogy developing schools of achievement for African American children - Murrell, Peter C.; NetLibrary, Inc. (Albany : State University of New York Press, 2002)
Based on a critical reinterpretation of several key educational frameworks, African-Centered Pedagogy is a practical guide to accomplished teaching. Murrell suggests integrating the historical, cultural, political, and developmental considerations of the African American experience into a unified system of instruction, bringing to light those practices that already exist and linking them to contemporary ideas and innovations that concern effective practice in African American communities. This is then applied through a case study analysis of a school seeking to incorporate the unified theory and embrace African-centered practice. Murrell argues that key educational frameworks-although currently ineffective with African American children-hold promise if reinterpreted.
Part 1: Framing the work -- The wrong frames for the right problem -- Traditions of African American education: a historical perspective -- Culture, cognition, and the community of achievement -- Part 2: Pedagogical theory for building a community of African American achievement -- Overview of the pedagogical theory -- From a community of caring to a community of achievement -- Teaching as assisted performances in the African American tradition -- The classroom ecology of culture and language -- Discourse practices in a community of achievement -- Teaching for understanding, learning for liberation -- Appraising my own practice: African-centered pedagogy in preparing teachers.
Includes bibliographical references (p. [181]-191) and index.
Electronic reproduction.
Keywords: African Americans -- Education; African Americans -- Race identity; Afrocentrism -- Study and teaching -- United States; Electronic books